The relationship of baseline high-sensitivity C-reactive protein with incident cardiovascular events and all-cause mortality over 20 yearsResearch in context - Adam Hartley; Somayeh Rostamian; Amit Kaura; Paris Chrysostomou; Paul Welsh; Cono Ariti; Naveed Sattar; Peter Sever; Ramzi Khamis (EBioMedicine)
Summary: Background: The prediction of future cardiovascular events in those with risk factors is important for the appropriate optimisation of preventative therapies for those at greatest risk. The value of high sensitivity C-reactive Protein (hsCRP) has been questioned in this regard. The objectives of this post-hoc analysis of a randomised controlled trial were to investigate the usefulness of baseline serum hsCRP for predicting very long-term cardiovascular events in patients with hypertension in the Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) Legacy Study. Methods: The ASCOT Legacy Study reports events up to 20 years of follow-up of the UK participants in the Lipid Lowering Arm of the original ASCOT trial. We examined outcomes related to serum hsCRP levels measured using a commercial ELISA, in tertiles or continuously, adjusting for classical cardiovascular risk factors as well as treatment allocation within ASCOT. The primary outcome was non-fatal myocardial infarction (MI) and fatal coronary heart disease (CHD); whilst secondary outcomes were all-cause mortality, total coronary events and procedures, total cardiovascular events and stroke. Findings: After excluding 3286 participants without hsCRP data, 5294 participants were included in the final cohort. The highest tertile of hsCRP was associated with the following outcomes compared to the lowest tertile: non-fatal myocardial infarction (MI) and fatal CHD (HR 1.32 [1.05–1.67]); total coronary events and procedures (HR 1.27 [1.09–1.47]); total cardiovascular events (HR 1.22 [1.08–1.37]); and all-cause mortality (HR 1.25 [1.10–1.42]). However, there was insufficient evidence regarding the association between hsCRP levels and stroke events. Addition of hsCRP in tertiles resulted in an improved net reclassification index for the prediction of non-fatal MI and fatal CHD at 20 years (9.68%, p < 0.0001). Interpretation: Higher baseline serum hsCRP levels can independently predict cardiovascular events and all-cause mortality at long-term follow-up in stable patients with hypertension. Funding: British Heart Foundation Clinical Research Fellowship (FS/17/16/32560), Wellcome Trust Clinical Research Fellowship (220572/Z/20/Z), and Sansour Fund at Imperial Healthcare Charity. The substudy of ASCOT Biomarker Programme was supported by Pfizer, New York, NY, USA. Infrastructure support was provided by the NIHR Imperial Biomedical Research Centre as well as the Imperial British Heart Foundation Research Excellence Award (4) (RE/24/130023).